KARAKTERISTIK RUANG TERBUKA SEBAGAI DAERAH RESAPAN DI KAWASAN SEKIP BENDUNG PALEMBANG - Ricky Ravsyan Alhafez (UNIVERSITAS INDO GLOBAL MANDIRI, 2014)
Sekip Bendung is one of the flood area . Some of the causes of flooding in this area is high rainfall and the unpreparedness of the area to absorb rainwater as quickly. This is because the level of development in this area is very high and the use of building materials that are not environmentally friendly.One solution to reduce the flood discharge is by making open space to both the public and private with the aim that rainwater can be absorbed into the soil. It also aims to change the paradigm of society which were initially how to keep the rain water as quickly - quickly discharged into the river becomes how to keep the rain water as quickly - quickly absorbed into the soil and also aims to preserve groundwater.With the aim of catchment areas is expected to arise from the characteristics of the open space that can be a guideline for planning - planning of open spaces in Palembang.